96.5k views
1 vote
f(x) = 2x2 + 6x - 4 9(2) = 573 – 6x2 – 3 Find (f +9)(2). O A. (f +g)(x) = -523 + 8x2 + 6x – 1 O B. (f +9)(x) = 5x3 + 2x2 – 7 O C. (f+g)(x) =1723 – 7 O D. (f + g)(x) = 5x3 - 4x2 + 6x - 7

f(x) = 2x2 + 6x - 4 9(2) = 573 – 6x2 – 3 Find (f +9)(2). O A. (f +g)(x) = -523 + 8x-example-1
User Richard YS
by
4.8k points

1 Answer

5 votes

Answer:

The function (f+g)(x) is:


(f+g)(x)=5x^3-4x^2+6x-7

Step-by-step explanation:

Given the functions;


\begin{gathered} f(x)=2x^2+6x-4 \\ g(x)=5x^3-6x^2-3 \end{gathered}

We want to find the function (f+g)(x);


\begin{gathered} (f+g)(x)=f(x)+g(x) \\ (f+g)(x)=(2x^2+6x-4)+(5x^3-6x^2-3) \\ (f+g)(x)=5x^3+2x^2-6x^2+6x-4-3 \\ (f+g)(x)=5x^3-4x^2+6x-7 \end{gathered}

Therefore, the function (f+g)(x) is:


(f+g)(x)=5x^3-4x^2+6x-7

User Kofi Sammie
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.